SYAIR LAGU DALAM PENGAJARAN SASTRA - Widawati, Rika (Prodi Teknologi Pendidikan, 2014)
Abtstract, literary work is an expression and reflection of life. By understanding the literary work people can try to uncover and understand what life is, seeing and understanding the world. Literature teaching is to teach the value of life. Teaching literature is aimed at fostering students in appreciating literature to develop their personality, knowledge, and reasoning power.Keywords: literature, teaching, song lyrics.Abstrak, karya sastra merupakan ekspresi dan cerminan kehidupan. Dengan memahami karya sastra akan mencoba mengungkap dan memahami hidup, melihat dan memahami dunia. Mengajarkan sastra pada hakikatnya adalah mengajarkan nilai kehidupan. Pengajaran sastra bertujuan membina siswa dalam mengapresiasi sastra untuk mengembangkan kepribadian, wawasan yang luas, dan daya nalar.Kata kunci: sastra, pengajaran, lirik lagu.